1995
DOI: 10.1074/jbc.270.28.16974
|View full text |Cite
|
Sign up to set email alerts
|

Topological Mapping of Neutrophil Cytochrome b Epitopes with Phage-display Libraries

Abstract: Cytochrome b of human neutrophils is the central component of the microbicidal NADPH-oxidase system. However, the folding topology of this integral membrane protein remains undetermined. Two random-sequence bacteriophage peptide libraries were used to map structural features of cytochrome b by determining the epitopes of monoclonal antibodies (mAbs) 44.1 and 54.1, specific for the p22phox and gp91phox cytochrome b chains, respectively. The unique peptides of phage selected by mAb affinity purification were ded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
133
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 153 publications
(134 citation statements)
references
References 42 publications
1
133
0
Order By: Relevance
“…Using a similar analysis, we found that monoclonal mouse anti-human gp91-phox [48] also recognized the bovine gp91-phox protein, resulting in a broad band of approximately 91 kDa. The smearing of gp91-phox in human and bovine samples is consistent with reported heterogeneous glycosylation of human gp91-phox [7], and the size of the bovine gp91-phox smear is approximately the same size as the human protein, suggesting a similar level of posttranslational glycosylation.…”
Section: Western Blot Analysis Of Bovine P22-phox and Gp91-phoxmentioning
confidence: 81%
See 1 more Smart Citation
“…Using a similar analysis, we found that monoclonal mouse anti-human gp91-phox [48] also recognized the bovine gp91-phox protein, resulting in a broad band of approximately 91 kDa. The smearing of gp91-phox in human and bovine samples is consistent with reported heterogeneous glycosylation of human gp91-phox [7], and the size of the bovine gp91-phox smear is approximately the same size as the human protein, suggesting a similar level of posttranslational glycosylation.…”
Section: Western Blot Analysis Of Bovine P22-phox and Gp91-phoxmentioning
confidence: 81%
“…For reference, prestained molecular weight standards (BRL, Bethesda, MD) were included on all gels. Immunoblots were probed with mouse monoclonal anti-human gp91-phox (54.1) [48] or rabbit polyclonal anti-human p22-phox [47], followed by Bio-Rad alkaline phosphatase-conjugated goat anti-mouse IgG or anti-rabbit IgG secondary antibodies, respectively. The blots were developed using a Bio-Rad alkaline phosphatase development kit.…”
Section: Electrophoresis and Western Blot Analysismentioning
confidence: 99%
“…Human neutrophils were prepared from fresh whole blood collected in citrate anticoagulant from normal human donors and probed by mAbs NL7, 44.1, 7D5, or an irrelevant isotype-matched monoclonal as described (6). Briefly, leukocytes were incubated in 200 nM of each mAb diluted in 10 mM PBS (10 mM phosphate, 150 mM NaCl, pH 7.4) with 4% normal goat serum and 4% nonfat dry milk for 30 min on ice.…”
Section: Flow Cytometrymentioning
confidence: 99%
“…Cyt b -specific mAbs have been applied to identify solventaccessible regions on both the cytosolic and extracellular aspects of the native protein, as well as regions which are accessible only after denaturation (6,7). Tertiary structural elements of native Cyt b have further been determined by this method, revealing discontinuous regions of protein that are contained within a single epitope (8,9).…”
mentioning
confidence: 99%
“…5 We routinely use the following antibodies for immunofluorescence microscopy of human neutrophils [6][7][8][9][10]. To detect NADPH oxidase components, antibodies specific for p22 phox (mAb 44.1) and gp91 phox (mAb 54.1) [20,21] are now available from Santa Cruz Biotechnology (Santa Cruz, CA); mAb 7D5 detects an epitope of gp91 phox present in mature flavocytochrome b 558 [22] and can be used on intact PMNs to detect protein upregulation at the cell surface [7]; a rabbit mAb specific for human p40 phox (Epitomics, Burlingame, CA); an antibody that specifically detects active Rac (NewEast Biosciences, Malvern, PA); and rabbit antisera from William Nauseef (University of Iowa) specific for p47 phox and p67 phox [6]. Mouse mAbs specific for human CD63, lamp-1, and CD11b are obtained from the University of Iowa Developmental Studies Hybridoma Bank.…”
mentioning
confidence: 99%